Literature Analysis on Classroom Management in Early Childhood Education in Indonesia - Kusumaningtyas, Nila; Aprianto, Ronal (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Effective classroom management in Early Childhood Education (ECE) in Indonesia is vital for creating a structured and engaging learning environment that accommodates the diverse cultural backgrounds and developmental needs of young learners. This study explores classroom management strategies at the ECE level through a comprehensive literature review, focusing on their role in fostering cognitive, social, and emotional development. By analyzing scientific articles, journals, and research reports, this research identifies key strategies, including: (1) play-based learning approaches, (2) flexible and responsive classroom layouts, (3) effective teacher-child communication, and (4) the development of self-regulation through consistent routines. The findings reveal that effective classroom management enhances children’s engagement, reduces behavioral issues, and promotes an inclusive and positive learning atmosphere. This study underscores the importance of culturally relevant approaches and offers practical insights for educators, policymakers, and curriculum developers. It also highlights the need for continuous teacher training to improve classroom management competencies. By addressing gaps in the existing literature, this research contributes to the development of tailored frameworks for Indonesia’s diverse educational context, ultimately supporting improved learning outcomes for young children.